HUKUM INTERNASIONAL SEBAGAI SUMBER HUKUM DALAM HUKUM NASIONAL (Dalam Perspektif Hubungan Hukum Internasional Dan Hukum Nasional Di Indonesia) - Sunyowati, Dina (Jurnal Hukum dan Peradilan, 2013)
Countries agreement contained in an international agreement in the form of bilateral agreements, regional and multilateral agreements that are binding on the parties and a law for that entered into an agreement (pacta sunt servanda). International agreements that have been agreed and validated in a ratification by a country, then the agreement is valid and binding upon all be a source of law for the enforcement of law in making decisions. This is true also in Indonesia. Any international agreement that has been followed by Indonesia, which is contained in a ratification requirement or not, still have the force of binding for both parties. Keywords: International Law, Sources of Law, International Treaties, International Agreements.